Perancangan Fakultas Hukum Universitas Negeri Gorontalo dengan Pendekatan Arsitektur Tropis - Mohamad Bayu Wahyudi Husain; Niniek Pratiwi; Rahmayanti (Transbahasa, 2026)
The increase in the number of students and academic activities at the Faculty of Law, Gorontalo State University (UNG) has not been matched by the availability of adequate facilities and infrastructure. The existing buildings are limited in terms of space capacity, thermal comfort, and learning environment quality, resulting in a less than optimal learning process. In addition, the existing buildings are not fully adapted to the tropical climate, which is characterized by high temperatures, high humidity, and high rainfall throughout the year. Therefore, it is necessary to redesign the Gorontalo State University Faculty of Law building in a way that addresses these issues in a functional and sustainable manner. This design aims to formulate a design concept for the UNG Faculty of Law using a Tropical Architecture approach that is responsive to the climate and capable of improving thermal comfort, energy efficiency, and the quality of learning spaces. The methods used in the design include field observations, literature studies, comparative studies, and analysis of site data, space requirements, structure, and building utilities. The design results emphasize the processing of building mass orientation, optimization of cross ventilation and natural lighting, use of secondary skin elements, application of voids as vertical ventilation, and provision of green open spaces as microclimate controllers. The application of this Tropical Architecture approach is expected to produce a comfortable, functional, energy-efficient, and sustainable Faculty of Law building that supports academic activities at Gorontalo State University.